Shear bond strength of a ceramic to Co-Cr alloys - Joias, Renato Morales; Tango, Rubens Nisie [UNESP]; Junho de Araujo, Jose Eduardo; Junho de Araujo, Maria Amelia; Ferreira Anzaloni Saavedra, Guilherme de Siqueira; de Arruda Paes-Junior, Tarcisio Jose; Kimpara, Estevão Tomomitsu [UNESP] (Mosby-elsevier, 2008)
Statement of problem. Different combinations of Co-Cr alloys bonded to ceramic have been used in dentistry; however, the bond strength of ceramic to metal can vary because of different compositions of these alloys.Purpose. The purpose of this study was to evaluate the shear bond strength of a dental ceramic to 5 commercially available Co-Cr alloys.Material and methods. Five Co-Cr alloys (IPS d.SIGN 20, IPS d.SIGN 30, Remanium 2000, Heranium P, and Wirobond C) were tested and compared to a control group of an Au-Pd alloy (Olympia). Specimen disks, 5 mm high and 4 mm in diameter, were fabricated with the lost-wax technique. Sixty specimens were prepared using opaque and dentin ceramics (VITA Omega 900), veneered, 4 mm high and 4 mm in diameter, over the metal specimens (n = 10). The shear bond strength test was performed in a universal testing machine with a crosshead speed of 0.5 mm/min. After shear bond testing, fracture surfaces were evaluated in a stereomicroscope under x25 magnification. Ultimate shear bond strength (MPa) data were analyzed with 1-way ANOVA and the Tukey HSD test (alpha = .05).Results. The mean (SID) bond strengths (MPa) were: 61.4 (7.8) for Olympia; 94.0 (18.9) for IPS 20; 96.8 (10.2) for I PS 30; 75.1 (12.4) for Remanium; 71.2 (14.3) for Heranium P; and 63.2 (10.9) for Wirobond C. Mean bond strengths for IPS 20 and IPS 30 were not significantly different, but were significantly (P<.001) higher than mean bond strengths for the other 4 alloys, which were not significantly different from each other.Conclusions. Bond strength of a dental ceramic to a Co-Cr alloy is dependent on the alloy composition.